A stable chemical SUMO1-Ubc9 conjugate specifically binds as a thioester mimic to the RanBP2-E3 ligase complex - Sommer, Stefanie; Ritterhoff, Tobias; Melchior, Frauke; Mootz, Henning D. (ChemBioChem, 2015)
Abstract Ubiquitin and ubiquitin-like (Ubl) modifiers such as SUMO are conjugated to substrate proteins by E1, E2, and E3 enzymes. In the presence of an E3 ligase, the E2?Ubl thioester intermediate becomes highly activated and is prone to chemical decomposition, thus making biochemical and structural studies difficult. Here we explored a stable chemical conjugate of the E2 enzyme from the SUMO pathway, Ubc9, with its modifier SUMO1 as a structural analogue of the Ubc9?SUMO1 thioester intermediate, by introducing a triazole linkage by biorthogonal click chemistry. The chemical conjugate proved stable against proteolytic cleavage, in contrast to a Ubc9?SUMO1 isopeptide analogue obtained by auto-SUMOylation. Triazole-linked Ubc9?SUMO1 bound specifically to the preassembled E3 ligase complex RanBP2/RanGAP1*SUMO1/Ubc9, thus suggesting that it is a suitable thioester mimic. We anticipate interesting prospects for its use as a research tool to study protein complexes involving E2 and E3 enzymes.